PENGARUH PENEMPATAN, BEBAN KERJA DAN KOMPENSASI TERHADAP KEPUASAN KERJA KARYAWAN PADA BPJS KETENAGAKERJAAN KANTOR CABANG PEKANBARU KOTA - Saputra Irfan; Nuryanti Nuryanti; Ningsih Suryati Dewita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of placement, workload and compensation on employee job satisfaction at BPJS Ketenagakerjaan Pekanbaru City Branch Office. The population in this study includes all employees at the BPJS Ketenagakerjaan Branch Office Pekanbaru City, totaling 62 people. Primary data was collected by using a questionnaire as an instrument to prove the results of the study, to test the hypothesis in this study using multiple linear regression analysis with the help of the SPSS program. The sampling technique that has been selected is the saturated sampling technique. The results of this study indicate that: 1) there is no effect of placement on the job satisfaction of employees of BPJS Ketenagakerjaan Branch Office Pekanbaru City, 2) there is a negative and significant effect of workload on job satisfaction of employees of BPJS Ketenagakerjaan Branch Office Pekanbaru City, 3) there is a positive and significant effect significant compensation on job satisfaction BPJS Ketenagakerjaan Branch Office Pekanbaru City, 4) there is a joint influence of placement, workload and compensation on job satisfaction BPJS Ketenagakerjaan Branch Office Pekanbaru City.Keywords: Placement, Workload, Compensation, Job Satisfaction